2019
DOI: 10.31235/osf.io/v58zr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Meta-Analysis of the Effectiveness of Health Belief Model Variables in Predicting Behavior

Abstract: The Health Belief Model (Rosenstock, 1966) was constructed to explain which beliefs should be targeted in communication campaigns to cause positive health behaviors. The model specifies that if individuals perceives a negative health outcome to be severe, perceives themselves to be susceptible to it, perceives the benefits to behaviors which reduce the likelihood of that outcome to be high, and perceives the barriers to adopting those behaviors to be low, then the behavior is likely. A meta-analysis of 18 stud… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
147
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(162 citation statements)
references
References 5 publications
9
147
3
3
Order By: Relevance
“…To further explore the direct and indirect effect of HBM components on oral hygiene status, the path analysis was conducted. Previous research has tried to refine the model and the perceived barriers have been identified as a strong predictor for behaviors [37]. In fact, the dominant effect of perceived barriers on oral health status has also been confirmed [30].…”
Section: Discussionmentioning
confidence: 99%
“…To further explore the direct and indirect effect of HBM components on oral hygiene status, the path analysis was conducted. Previous research has tried to refine the model and the perceived barriers have been identified as a strong predictor for behaviors [37]. In fact, the dominant effect of perceived barriers on oral health status has also been confirmed [30].…”
Section: Discussionmentioning
confidence: 99%
“…Beneficiaries who reported lacking a usual health care provider accounted for about one-quarter of beneficiaries with undiagnosed conditions in our sample. Our analysis builds on previous investigations of the relationship between health beliefs and health care seeking behaviors and provides several methodological advantages with respect to studying Medicare beneficiaries ( Janz and Becker 1984;Carpenter 2010;Edwards 2013). First, due to the merge of REGARDS data with Medicare claims, we were able to track participants' awareness of health conditions and health care utilization in the months directly before and after assessment, and to measure health care utilization prospectively using Medicare claims rather than retrospectively using self-reported data.…”
Section: Discussionmentioning
confidence: 99%
“…Rosentock (Carpenter 2010) memaparkan empat komponen dasar dari HBM, antara lain perceived susceptibility, perceived severity, perceived benefits, serta perceived barriers. Komponen pertama yaitu perceived susceptibility menjelaskan bahwa individu akan termotivasi melakukan perilaku jika mereka percaya bahwa mereka memiliki kerentanan untuk terkena dampak negatif dari suatu penyakit atau masalah tertentu di dalam konteks kesehatan atau kesejahteraan diri.…”
Section: Pendahuluanunclassified
“…Menurut Carpenter (2010) Perceived Benefit dan Perceived Barrier hampir selalu menjadi variabel yang memiliki kontribusi terkuat dalam memprediksi perilaku di dalam banyak penelitian Health Belief Model. Namun, di dalam penelitian ini hanya Perceived Barrier yang menjadi prediktor terkuat.…”
Section: Hasil Dan Pembahasanunclassified